Irresolute clay : shaping the foundations of modern environmental law - Macrory, Richard (London [England] : Hart Publishing, 2020)
"At a time of profound change and rethinking, this book provides insights into how environmental law in the UK has developed into its current form, and considers challenges it will face in the future. Irresolute Clay is not a legal history or textbook, nor a conventional set of legal memoirs. Instead it offers a personal account of the inside stories as experienced by one of the key architects of contemporary environmental law. Taking a thematic approach, it charts fundamental tenets of the subject (such as environmental sanctions, the European dimension, developing the academic discipline of environmental law, and environmental courts and tribunals), from the beginnings of the modern environmental law era in the 1970s to the present day."--
13. Brexit and Environmental Law -- Published Works by Richard Macrory -- Index
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Environmental law -- Great Britain -- History; Environmental lawyers -- Great Britain -- Biography; International environmental law; Electronic books